2021
DOI: 10.1038/s41420-021-00751-2
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload in endometriosis peritoneal fluid induces early embryo ferroptosis mediated by HMOX1

Abstract: Endometriosis is one of the most common disorders that causes infertility in women. Iron is overloaded in endometriosis peritoneal fluid (PF), with harmful effects on early embryo development. However, the mechanism by which endometriosis peritoneal fluid affects embryonic development remains unclear. Hence, this study investigated the effect of iron overload on mouse embryos and elucidated the molecular mechanism. Iron overload in endometriosis PF disrupted blastocyst formation, decreased GPX4 expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 40 publications
(42 reference statements)
0
45
0
Order By: Relevance
“…Additionally, endometriosis PF's iron excess prevents blastocyst development and damages developing embryos by causing ferroptosis and mitochondrial malfunction. 59,63 The consequences of iron excess on embryo development have been the subject of numerous studies, although the precise connection between ferroptosis and embryotoxicity has not yet been established. According to a study, HMOX1 is elevated during embryonic ferroptosis and inhibits it by maintaining mitochondrial activity and protect them from oxidative stress.…”
Section: The Two Sides Effects Of Ferroptosis In Emsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, endometriosis PF's iron excess prevents blastocyst development and damages developing embryos by causing ferroptosis and mitochondrial malfunction. 59,63 The consequences of iron excess on embryo development have been the subject of numerous studies, although the precise connection between ferroptosis and embryotoxicity has not yet been established. According to a study, HMOX1 is elevated during embryonic ferroptosis and inhibits it by maintaining mitochondrial activity and protect them from oxidative stress.…”
Section: The Two Sides Effects Of Ferroptosis In Emsmentioning
confidence: 99%
“…According to a study, HMOX1 is elevated during embryonic ferroptosis and inhibits it by maintaining mitochondrial activity and protect them from oxidative stress. 63 When considered collectively, we cannot ignore the impact of ferroptosis for the subsequent pathologic processes of EMs.…”
Section: The Two Sides Effects Of Ferroptosis In Emsmentioning
confidence: 99%
“…Ferroptosis could be triggered during development or during normal homeostatic tissue turnover, by the accumulation of (1) iron [ 25 , 26 , 27 , 28 , 29 ] or (2) PUFAs [ 17 ], or by (3) the depletion of the antioxidant glutathione (GSH) [ 30 ], decreased function of glutathione peroxidase 4 (GPX4), which mediates the reduction of lipid peroxides [ 31 , 32 ], or the activation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase [ 33 , 34 , 35 ].…”
Section: Ferroptosis and Mechanismsmentioning
confidence: 99%
“…Ferroptosis as an iron-dependent form of non-apoptotic cell death [ 6 ], and it is closely linked to endometriosis attributed to its high iron environment. A recent study reported that overloaded iron in endometriosis peritoneal fluid (PF) had harmful effects on the development of early embryos [ 7 ]. Our recent study has reported that follicular fluid (EMFF) with iron overload induces ferroptosis of granulosa cells and oocyte dysmaturity, and further contributes to EM-related infertility [ 8 ].…”
Section: Introductionmentioning
confidence: 99%